1996
DOI: 10.1530/jrf.0.1070175
|View full text |Cite
|
Sign up to set email alerts
|

Embryo viability, duration of gestation and birth weight in sheep after transfer of in vitro matured and in vitro fertilized zygotes cultured in vitro or in vivo

Abstract: The influence of various in vitro procedures on embryo survival and the production of normal offspring was investigated in sheep. Zygotes with both in vivo cultured IVM\p=n-\IVF zygotes and control zygotes 25\p=n-\35% versus 51\p=n-\60%, respectively, P < 0.05). Day 6.5 IVM\p=n-\IVFmorulae had a lower survival rate than did control morulae regardless of culture treatment (P < 0.05), while survival rates of day 6.5 IVM\p=n-\IVF blastocysts cultured in vivo did not differ from those of control blastocysts (P >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 12 publications
5
55
1
14
Order By: Relevance
“…Similar findings after the transfer of in vitro produced embryos have been reported previously for sheep (Walker et al 1992, Thompson et al 1995, Holm et al 1996, Brown & Radziewic 1998. A number of factors have been implicated in the birth of large offspring after ET of in vitro produced embryos (reviewed by Walker et al 1992Walker et al , 1996 including asynchronous ET (Wilmut & Sales 1981), particularly after the transfer of vitrified embryos (Naitana et al, 1995, Leoni et al 2003, progesterone treatment of ewes early in gestation (Kleeman et al 1994) and the use of serum as the source of protein during in vitro culture (Thompson et al 1995).…”
Section: Discussionsupporting
confidence: 69%
“…Similar findings after the transfer of in vitro produced embryos have been reported previously for sheep (Walker et al 1992, Thompson et al 1995, Holm et al 1996, Brown & Radziewic 1998. A number of factors have been implicated in the birth of large offspring after ET of in vitro produced embryos (reviewed by Walker et al 1992Walker et al , 1996 including asynchronous ET (Wilmut & Sales 1981), particularly after the transfer of vitrified embryos (Naitana et al, 1995, Leoni et al 2003, progesterone treatment of ewes early in gestation (Kleeman et al 1994) and the use of serum as the source of protein during in vitro culture (Thompson et al 1995).…”
Section: Discussionsupporting
confidence: 69%
“…In vitro embryo production is not viewed as a controlled and totally defined technique and in sheep has been associated with the large offspring syndrome (LOS) [20,104], also reported in other species such as bovine [105]. This syndrome is characterized by high birth weights, increased gestation length, frequent dystocia, elevated abortion, perinatal mortality rates, and various morphological deviations [20,106].…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…This syndrome is characterized by high birth weights, increased gestation length, frequent dystocia, elevated abortion, perinatal mortality rates, and various morphological deviations [20,106]. These abnormalities seem to be promoted very early in developmental stages, in IVM or IVF [3,104], and apparently can be justified by the use of serum supplementation and coculture with somatic cells [3]. Moreover, these problems could be extended after birth, as higher growing rates were found until weaning age in lambs born from IVP [107].…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…Addition of fetal bovine serum (FBS) on day 2 or 3 of culture does result in high embryo survival post-embryo transfer and normal viable offspring [41]. However, some studies have reported that sheep embryos reduce their viability by 15%-25% when produced in SOF systems supplemented with serum compared to co-culture [48] or in in vivo systems of culturing the embryos in oviducts [49]. It has been noted that adding steer serum or human serum to sheep and goat IVC media may attribute to many abnormalities in the offspring [50,51].…”
Section: In Vitro Culturementioning
confidence: 99%